Analisa Kerusakan Gear Countershaft Transmision pada Sepeda Motor ANF 125 dan Optimasi Umur Pakai - Diyanto, Muhammad Isro (Universitas Pamulang, 2024)
Gear countershaft transmission on the motorcycle engine serves to move the rotary power from input shaft to gear acceleration. Damage to wear and tear on the eyes of the gears and broken on the eyes of the gears. In the event of damage, the tooth will be difficult to move, the transmission jumps out of the tooth, the engine does not work optimally and the engine raises noises.With visual observations of damage to gear countershaft, tests should be performed to ensure the cause of the damage includes testing of material composition, hardness test, tensile test and metallographic tests and microstructure observations. Analysis of test results is compared with the literature, international material standard, perm simulation and other supporting factors are expected to be the right decision reference on the main cause of the damage The conclusions of the main causes of damage are used for the development of extending life time including material improvements, manufacturing, installation methods and the adoption of appropriate maintenance management systems.